Hydrotherapy and acupressure in restless legs syndrome: results of a randomized, controlled, three-armed, pilot study (HYDRAC-study) - Julia Kubasch; Miriam Ortiz; Sylvia Binting; Stephanie Roll; Katja Icke; Joanna Dietzel; Rainer Nögel; Josef Hummelsberger; Stefan N. Willich; Benno Brinkhaus; Michael Teut; Julia Siewert (Frontiers in Medicine)
Study objectivesNon-pharmacological interventions for restless legs syndrome (RLS) are frequently used, although scientific evidence remains limited. The study aimed to investigate the feasibility and effects of self-applied hydrotherapy and self-applied acupressure in patients with RLS.MethodsIn a three-armed randomized single-center open exploratory pilot study, adults with moderate to severe RLS were randomly allocated to 6 weeks of daily hydrotherapy plus routine care (HT group), acupressure plus routine care (AP group), or routine care alone (RC group). Outcome measures included RLS symptom severity (IRLS), disease-specific quality of life (RLSQoL), the impression of change (PGI-C), health-related quality of life (SF-12), psychological outcomes (SGW-B, HADS, and GSE), and adherence and adverse events (AEs) after 6 and 12 weeks.ResultsFifty-four adults (mean age 57.5 ± 11.4 years, 63% women) were included. The study showed good feasibility with an 83% retention rate. After 6 weeks, baseline-adjusted mean IRLS scores were 19.8 (95% [16.4, 23.2]) for HT, 22.9 (19.2, 26.6) for AP, and 24.0 (20.8, 27.2) for RC. RLSQoL adjusted means were 65.3 (59.7, 70.9) for HT, 68.3 (62.3, 74.3) for AP, and 56.2 (50.9, 61.5) for RC, after 6 weeks. Both interventions were safe, with high adherence rates.ConclusionSelf-applied hydrotherapy and acupressure appear to be feasible and safe interventions for patients with RLS. This exploratory pilot study suggests potential benefits, though larger, well-designed confirmatory studies are needed to validate these findings.Clinical trial registrationThis study was registered in the German Clinical Trials Register (number DRKS00029960) on August 09, 2022. https://drks.de/search/de/trial/DRKS00029960.